Morphological variability of the nanoplanktonic diatom Thalassiosira laevis from coastal waters of Province of Buenos Aires (Argentina) - Sar, Eugenia Alicia (2017)
Morphological variability of the nanoplanktonic diatom Thalassiosira laevis from coastal waters of Province of Buenos Aires (Argentina). Despite the fact that the genus Thalassiosira was previous and extensively studied including ultrastructural analysis of species found in phytoplanktonic samples collected from marine waters of Argentina, nanoplanktonic species have been frequently overlooked. This paper is devoted to show the morphological variation of Thalassiosira laevis, a nanoplanktonic species collected from marine coastal waters of the Province of Buenos Aires, to compare Argentinean material with those from China, Korea and Brazil described in the literature, and to record it for the first time from Argentina.